Sarah Kay and the voices of childhood in contemporary narrative regarding memory (Anclajes, 2020)
The novel Matilde (2016) by Carola Martínez Arroyo and the story "El ahorcado" (2016) by Mariana Enríquez recapture Sarah Kay drawings to portray childhoods affected by the Chilean and Argentine dictatorships. Our goal is to study the way in which these drawings are appropriated and given new meaning in children’s stories in order to communicate political violence. Based on studies in the field of memory, and with contributions from Paula Caldo (2015) on print culture and the education of female children, this article analyzes how Martínez Arroyo and Enríquez’s texts organize their narratives to challenge the joyful world proposed by a market intended for children and everyday life in the context of dictatorial processes.
Keywords: Carola Martínez Arroyo; Mariana Enríquez; Argentina; Chile; memories